2009
DOI: 10.1172/jci36460
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte elevated gene-1 regulates hepatocellular carcinoma development and progression

Abstract: Hepatocellular carcinoma (HCC) is a highly aggressive vascular cancer characterized by diverse etiology, activation of multiple signal transduction pathways, and various gene mutations. Here, we have determined a specific role for astrocyte elevated gene-1 (AEG1) in HCC pathogenesis. Expression of AEG1 was extremely low in human hepatocytes, but its levels were significantly increased in human HCC. Stable overexpression of AEG1 converted nontumorigenic human HCC cells into highly aggressive vascular tumors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
563
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(586 citation statements)
references
References 76 publications
23
563
0
Order By: Relevance
“…Moreover, the expression of MTDH increases in malignant glioma and MTDH regulates in vitro invasion and migration of malignant glioma cells by activating the nuclear NF-kappaB signaling pathway (Sarkar et al, 2008). In addition, MTDH was also found to activate Wnt/ beta-catenin signaling pathway via ERK42/44 activation and upregulated lymphoid-enhancing factor 1/T cell factor 1 (LEF1/TCF1), the ultimate executor of the Wnt pathway, important for Hepatocellular carcinoma progression (Yoo et al, 2009). Further more, Microarray analysis of breast cancer cells revealed that MTDH knockdown led to decreased expression of chemoresistance genes ALDH3A1, MET, HSP90, AND HMOX1, and increased expression of pro-apoptotic genes BNIP3 and TRAIL MTDH was thought to be a potential focus for targeted therapy based on its multi-facet roles in regulating cancer apoptosis, invasion, metastasis, and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of MTDH increases in malignant glioma and MTDH regulates in vitro invasion and migration of malignant glioma cells by activating the nuclear NF-kappaB signaling pathway (Sarkar et al, 2008). In addition, MTDH was also found to activate Wnt/ beta-catenin signaling pathway via ERK42/44 activation and upregulated lymphoid-enhancing factor 1/T cell factor 1 (LEF1/TCF1), the ultimate executor of the Wnt pathway, important for Hepatocellular carcinoma progression (Yoo et al, 2009). Further more, Microarray analysis of breast cancer cells revealed that MTDH knockdown led to decreased expression of chemoresistance genes ALDH3A1, MET, HSP90, AND HMOX1, and increased expression of pro-apoptotic genes BNIP3 and TRAIL MTDH was thought to be a potential focus for targeted therapy based on its multi-facet roles in regulating cancer apoptosis, invasion, metastasis, and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…AEG‐1/MTDH was subsequently found to mediate the metastasis of breast cancer 8. In recent years, AEG‐1 expression was found to be elevated and correlated with clinical tumour type, stage, metastasis and prognosis in a variety of cancers, including breast 9, lung 10, colorectal 11, cervical 12, 13, head and neck 14, hepatocellular 15 and gastric cancers 16, 17. AEG‐1 has been shown to be transcriptionally up‐regulated by Ha‐Ras‐activated PI3K and c‐Myc 18.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between localization of MTDH and its function is not clear. While in breast cancer (Li et al, 2008), HCC (Yoo et al, 2009) and melanoma (Sarkar et al, 2009) increased MTDH nuclear staining is associated with advanced disease, in prostate cancer (Thirkettle et al, 2009), decreased nuclear staining is related to poor prognosis.…”
Section: Deregulation Of Mtdh Gene Expression In Gastric Cancermentioning
confidence: 98%
“…Activation of NF-κB , PI3K/AKT (Lee et al, 2006), MAP kinase and Wnt/β-catenin (Yoo et al, 2009) signal tarnsduction pathways by MTDH induces specific phenotypes including cell survival, anti-apoptosis, angiogenesis, migration and invasion in various cell types (Sarkar et al, 2009). More recently, Li et al have shown that over-expression of MTDH leads to increased acquisition of cancer stem cell markers in breast cancer cells (Li et al, 2011).…”
Section: Deregulation Of Mtdh Gene Expression In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation